HTERT gene expression levels and telomerase activity in drug resistant MCF-7 cells - Sakin, V.; Eskiocak, U.; Kars, M.D.; Iseri, Ö.D.; Gunduz, U. (Experimental Oncology, 2008)
Cancer cells and some highly proliferative normal cells can stabilize telomere lengths by telomerase, which adds hexameric repeats to the ends of linear chromosomes. In this study, the activity of telomerase reverse transcriptase (hTERT) and its gene expression levels were investigated in paclitaxel, docetaxel, vincristine and doxorubicin resistant human MCF-7 breast adenocarcinoma cells. Materials and Methods: Resistant cell lines were developed by stepwise selection of cells (MCF-7/S) in increasing doses of paclitaxel (MCF-7/Pac), docetaxel (MCF-7/Doc), vincristine (MCF-7/Vinc) and doxorubicin (MCF-7/Dox). Antiproliferative effects of anticancer drugs were evaluated by XTT assay and IC50 values for different drugs were determined from cell proliferation curves. Expression levels of hTERT gene in sensitive and resistant cells were analyzed by RT-PCR. TRAP-Silver Staining assay was used to evaluate telomerase activities in these cells. Results: When drug resistant and sensitive MCF-7 cells were compared no significant differences were observed in hTERT expression levels and telomerase enzyme activities. Conclusion: This report demonstrates that drug resistance developed against paclitaxel, docetaxel, vincristine and doxorubicin in MCF-7 cells is independent of the expression of hTERT gene and telomerase activity.